Catalina León Pesántez, Hispanoamérica y sus paradojas en el ideario filosófico de Juan León Mera, Universidad Andina Simón Bolivar/Corporación Editora Nacional, Abya-Yala, Serie Magister, No. 16, QUITO, 2001, 94 pp. - Ayala Mora, Enrique (Procesos. Revista Ecuatoriana de Historia, 2001)
s.r.